The Effect of Driving Factor to Intention to Use Augmented Reality Application for Data Supporting in Sales Promotion the Non-Performing Asset of Financial Institutions in Thailand - Poolmuangrat, Poonsak; Meechaisue, Prayong; Charuphathiran, Supasith; Jinandech, Norapon (Ph.D. in Social Sciences Journal, 2020)
The research objectives were (1) to study the effects of driving factor on perceived value, perceived risk and intention to use. (2) to study the effects of perceived value on intention to use. (3) to study the effects of perceived risk on intention to use. Is a mixed-methods research. The sample used in quantitative research is the officers or employees of the financial institution that sells non-performing asset (NPA) in Thailand, a total of 506 people, by analyzing the data using statistic, percentage, average, standard deviation. coefficient of variation and structural equation analysis by using the factor analysis technique, while the qualitative research uses in-depth interviews from actual sites and observations. With executives in organizations operating in the business of selling non-performing asset by financial institutions in Thailand total 7 persons. The result of quantitative research reveals that the driving factor have a direct positive impact on perceived value and intention to use significantly and perceived value had a direct positive effect on the intention to use in terms of statistical significance. It was also found that the result of qualitative research is accordingly to the result of quantitative research as above.